Weed Control in Tomato - William M. Stall (EDIS)
Revised! HS-200, a 5-page fact sheet by William M. Stall, explains the increased importance of weed management in tomato production due to the introduction of the sweet potato whitefly. It discusses management in all areas of the farm, as well as post-harvest vine desiccation. Includes a table listing chemical weed controls for tomatoes in Florida. Published by the UF Department of Horticultural Sciences, November 2007.